Remembering the Summer of 2020. Issue 4 (18th August 2020) - Denton‐Borhaug, Kelly
Abstract: How will historians and theologians remember the summer of 2020? This article leverages a socio‐ethical analysis and response to twenty years of sacralized and sacrificial U.S. war‐culture, and the meaning of this history, given the shifting cultural tectonic plates in the summer of 2020, and intersecting social ills of climate crisis, racism, inequality, and pandemic.